2015
DOI: 10.1111/bcp.12635
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant associated with paracetamol overdose: results from the seven‐country SALT study

Abstract: Paracetamol overdose was found to represent one-sixth of all-cause ALFT. There was a 50-fold difference in Europe in the rates of paracetamol overdose ALFT, and a 200-fold difference per million inhabitants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 27 publications
0
57
0
4
Order By: Relevance
“…The primary cause of these intoxications is acetaminophen (38). Liver toxicity linked to acetaminophen is dose-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…The primary cause of these intoxications is acetaminophen (38). Liver toxicity linked to acetaminophen is dose-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…In the UK and North America, paracetamol overdosage has been the leading cause of ALF [5, 6]. In parts of Europe (e.g., Germany and Portugal), the most common causes of ALF have been non-paracetamol drug-induced liver injury, seronegative (indeterminate) liver injury, and viruses (mostly hepatitis B) [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dominant etiology of ALF is not similar even among Western countries due to its highly variable epidemiologic pattern. In a study conducted by Gulmez et al it was found that acute drug overdose, mainly from acetaminophen, was the etiology for ALF in 20% of the causes in 7 European countries overall, but with a very variable range of prevalence from 1% in Italy to 52% in Ireland (16). In another study by Escorsell et al the incidence of acetaminophen induced ALF was reported to be very low (2.2%) in Spain (17).…”
Section: Discussionmentioning
confidence: 96%